Analysis Of The Impact Of Social Media Use On Character Education In The Era Of Society 5.0: A Literature Review - Siti Sahronih; Wirda Hanim; Utami Rosalina; Sadiah Maemuna (Departement of Mathematics Education, 2024)
The era of society 5.0 can be defined as a concept of society that is technology-based and human-centered. One technology that is currently developing rapidly is social media. The development of social media has had an impact on education, both negative and positive. This research aims to study the impact of using social media on character education. Data sources were collected based on journals related to the impact of social media use on character education published within the last five years. The method used is literature study. The research results show that unsupervised use of social media can have a negative impact on character education, these include: 1) students become indifferent to the surrounding environment; 2) students do not focus when following the teacher's instructions; 3) loss of student politeness; 4) students are lazy about doing assignments. Apart from that, social media has positive impacts such as: 1) increasing students' ability to work together and communicate; 2) train students' creativity; 3) through social media it can increase students' tolerance attitudes; and 4) through social media such as YouTube and google students can search for and repeat lessons. Thus, it can be concluded that the use of social media for character education in the era of society 5.0 has both negative and positive influences based on its use.